Measurement and Analysis of Interconnects’ Resonance and Signal/Power Integrity Degradation in Glass Packages - Youngwoo Kim (Micromachines)
In this article, resonance phenomena of high-speed interconnects and power delivery networks in glass packages are measured and analyzed. The resonances are generated in the interconnection by the physical dimension, cancelation of reactance components, and modes. When the resonances are generated in the operation frequency band, the signal/power integrity of the interconnect can be affected. As such, resonances generated in high-speed interconnects increase insertion loss, which degrades signal integrity. Also, resonances of the power delivery network (PDN) associated with boundary conditions increase PDN impedance, which degrades power integrity by generating power/ground noise and return current discontinuity of through vias. Recently, glass packaging has been gaining more attention due to its advantages associated with low substrate loss and large dimensions compared to silicon wafers. However, the low loss of the substrate and process variation may affect the resonance properties of interconnects. The resonance impacts on signal/power integrity must be analyzed, and mitigation plans should be proposed to maximize the advantages of the glass packaging technology. To analyze the resonance impacts on signal/power integrity, various glass package test vehicles are designed and fabricated. The fabricated test vehicles include transmission lines, PDNs, and patterns to measure an interaction between the through via and PDN. First, transmission line patterns that have 50-ohm characteristic impedance are measured. Due to the process variations, quarter-wave resonances are monitored, and at those frequencies, a sharp increase in insertion loss is observed, which deteriorates the signal integrity of the interconnect. Various PDN patterns are measured in the frequency domain, and regardless of the PDN shape, PDN impedance peaks are observed at the mode resonance frequencies. Due to a low-loss characteristic of the glass substrate, sharp PDN impedance peaks are generated at these frequencies. Also, at these frequencies, both signal and power integrity degradations are measured and analyzed. To fully benefit from the advantages of glass packaging technology, a thorough electrical performance analysis should be conducted to avoid resonances in the target frequency range.